Enhancing Physical Activity and Brain Reorganization after Stroke - Janet H. Carr; Roberta B. Shepherd (Neurology Research International)
It is becoming increasingly clear that, if reorganization of brain function is to be optimal after stroke, there needs to be a reorganisation of the methods used in physical rehabilitation and the time spent in specific task practice, strength and endurance training, and aerobic exercise. Frequency and intensity of rehabilitation need to be increased so that patients can gain the energy levels and vigour necessary for participation in physical activity both during rehabilitation and after discharge. It is evident that many patients are discharged from inpatient rehabilitation severely deconditioned, meaning that their energy levels are too low for active participation in daily life. Physicians, therapists, and nursing staff responsible for rehabilitation practice should address this issue not only during inpatient rehabilitation but also after discharge by promoting and supporting community-based exercise opportunities. During inpatient rehabilitation, group sessions should be frequent and need to include specific aerobic training. Physiotherapy must take advantage of the training aids available, including exercise equipment such as treadmills, and of new developments in computerised feedback systems, robotics, and electromechanical trainers. For illustrative purposes, this paper focuses on the role of physiotherapists, but the necessary changes in practice and in attitude will require cooperation from many others.